Development of two short measures for recovery and stress in sport. Issue 7 (9th August 2017) - Nässi, Anu; Ferrauti, Alexander; Meyer, Tim; Pfeiffer, Mark; Kellmann, Michael
Abstract: The Acute Recovery and Stress Scale (ARSS) and the Short Recovery and Stress Scale were first established in German for the purposes of monitoring athletes' current recovery-stress states in an economical and multidimensional manner. The aim of this paper is to document the development and initial validation of the English versions of these two psychometric monitoring tools. A total of 267 English-speaking athletes from a variety of team and individual sports participated in the study. The English versions demonstrated satisfactory internal consistency for both instruments (Cronbach α of .74–.89). Furthermore, good model fit was found for the eight scales of the ARSS, matching the structure and results of the German counterparts. Correlations among and between the scales reciprocate the theoretical constructs of stress and recovery, supporting the construct validity of the scales. Correlation coefficients within stress and recovery ranged between r s  = .29 and .68. The correlations between stress and recovery varied between r s  = −.29 and −.64. These constructs were further supported by correlations with the scores of the Recovery-Stress Questionnaire for Athletes, thereby showing convergent validity. The findings demonstrate initial validity and reliability of the two measures and reflect the results of the German versions. However, further research is needed before applying these scales in practical settings.